2007
DOI: 10.1002/tcr.20115
|View full text |Cite
|
Sign up to set email alerts
|

Partial reduction of pyrroles: application to natural product synthesis

Abstract: The partial reduction of N-Boc pyrroles has been explored giving stereoselective routes to disubstituted pyrrolines in good yields and with excellent diastereoselectivities. A novel methodology has been developed to carry out reductive aldol reactions on 2-substituted N-Boc pyrroles; use of aldehydes under reductive aldol conditions gave the anti aldol product in good selectivity. This chemistry was used as the key transformation in a synthesis of omuralide, which was achieved in 13 steps and 14% overall yield… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(17 citation statements)
references
References 37 publications
0
17
0
Order By: Relevance
“…To improve chemoselectivity, the procedure employing LiDBB reported by Donohoe and co-workers is notable since it is widely used for reduction of electron-deficient heteroarenes with good tolerance of esters, which seldom survives during Birch reduction. 17 This Communication discloses the finding that simply modifying the waveform of electrolysis (rapid alternating polarity, rAP) can lead to a new level of chemoselectivity for arene and heteroarene reduction. This operationally simple protocol proceeds at ambient temperature in protic solvent, does not require sacrificial electrodes, or even any metal source, and tolerates functional groups that are notoriously challenging to accommodate such as ester, nitrile, epoxide and even alkyl chloride.…”
Section: Main Textmentioning
confidence: 82%
“…To improve chemoselectivity, the procedure employing LiDBB reported by Donohoe and co-workers is notable since it is widely used for reduction of electron-deficient heteroarenes with good tolerance of esters, which seldom survives during Birch reduction. 17 This Communication discloses the finding that simply modifying the waveform of electrolysis (rapid alternating polarity, rAP) can lead to a new level of chemoselectivity for arene and heteroarene reduction. This operationally simple protocol proceeds at ambient temperature in protic solvent, does not require sacrificial electrodes, or even any metal source, and tolerates functional groups that are notoriously challenging to accommodate such as ester, nitrile, epoxide and even alkyl chloride.…”
Section: Main Textmentioning
confidence: 82%
“…The relativelyl ow yields found in some cases were due mainly to the reaction between the startingp henacyl iodide and methanol, leading to the formation of side products relatedt oc ompound 3.T his observation, and our previously stated goal to carry out the reaction under solvent-free conditions, prompted us to assay highspeed vibration milling (HSVM) activation.F urthermore, because of the existence of al iterature precedentf or the preparation of a-iodoketones from ketones and N-iodosuccinimide by grinding with am ortara nd pestle in the presence of toluenesulfonic acid, [37] we expectedt hat the HSVM protocol might allow the combinationo fb oth reactions into as inglep rocess, allowing the sequential multicomponent synthesis of pyrroles from very simple materials, namely ketones, primary amines, and b-dicarbonyl compounds. We carriedo ut the optimization work by investigating the preparation of compound 1r from acetophenone and ethyl 3-amino-2-butenoate, ac ommercially available b-enaminone,a nd found that av ibration frequency of 20 Hz was neededf or the reactiont oa chieve completion. Some excess( 1.5 equiv) of the enaminone was needed, probably to compensate for its partial hydrolysis by the water liberated in the final condensation, aided by the presence of the acid catalystrequired for the halogenationstep (Table 3).…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, pyrroles are also very important in the preparation of new materials [19] and they are also valuableb uilding blocks for the synthesis of alkaloids and unnatural heterocycles. [20] Pyrrole derivatives can be assembled by many methods, including the traditional Knorr,P aal-Knorr,a nd Hantzsch reactions. [21] These methods involver egioselectivity issues and are complicated by the low chemical stability of pyrroles, which often leads to their decomposition under many of the classical reactionc onditions.…”
Section: Introductionmentioning
confidence: 99%
“… 37 They are also important components in the production of alkaloids and artificial heterocycles. 38 Greater attention has been directed toward the production and application of pyrrole derivatives as dyes. 39 Furthermore, pyrroles have been claimed to be used in organic semiconductors.…”
Section: Introductionmentioning
confidence: 99%